National Trends in Endovascular Thrombectomy and Decompressive Craniectomy for Acute Ischemic Stroke: A Study Using National Inpatient Sample Data From 2006 to 2016. (16th November 2020) - McDougall, Riley; Gravbrot, Nicholas; Aguilar-Salinas, Pedro; Burket, Aaron; Dumont, Travis M
Abstract: INTRODUCTION: Ischemic stroke is a frequently encountered neurologic process with wide-spanning impact. A dreaded complication is cerebral edema, necessitating decompression to reduce herniation risk. Following the publication of several landmark trials in 2015, endovascular thrombectomy (EVT) with novel clot-removal devices has emerged as an effective treatment for proximal large vessel disease. METHODS: National Inpatient Sample (NIS) data was abstracted from 2006 to 2016. Primary outcomes were EVT and DC rates, compared using Cochrane-Armitage test of trend. Chi-square test was also used to compare data from 2015 to 2016. Secondary outcomes included inpatient mortality and home discharge rates. RESULTS: EVT rates steadily increased from 2006 to 2016, with most change occurring from 2014 to 2016 (1.36% in 2014, 2.29% in 2016). DC rates similarly increased from 2006 to 2015, though a sharp decline was observed in 2016 (0.42% in 2015, 0.22% in 2016). Test of trend from 2006 to 2016 for both variables was found to be statistically significant ( P < .05); DC rate change from 2015 to 2016 was also statistically significant ( P < .01). Mortality rate and home discharge rate steadily improved over the study period. CONCLUSION: Recent innovation in stroke treatment has led to increased EVTs. While DC rate initially followed this trend, wider adoption of novel EVT technologies led to a significant decline in 2016. These findings suggest that EVT may reduce the need for DC in acute stroke management.